DESIGN AND MODELING OF A SHORT -STROKE LINEAR PERMANENT MAGNET MOTOR - Isahak, Nor Haziana (Universiti Teknologi Petronas, 2010)
The thesis concentrates on design and modeling a short-stroke linear permanent magnet motor using finite element analysis. Various types of linear machines technologies have been review such as, linear induction motor, linear synchronous motor, linear switched reluctance motor, linear DC motor and linear permanent magnet brushless motor. The advantages of linear permanent magnet motor which are, there is no field winding required for the motor since the permanent magnet will produce the excitation flux for the motor. Even though it has higher cogging torque but it also has higher output power. In other aspect, the permanent magnet motor believe would give better dynamic performance due to the higher magnetic flux density in the air-gap. Four proposed design have been developed for further analysis; the single slot linear permanent magnet motor with air-cored and iron-cored also the double slot linear permanent magnet motor with air-cored and iron-cored. The design is relatively to improve efficiency of the compressor system for refrigerator pump, which basically have very low efficiency. The proposed design undergoes the optimization process with optimizing the dimension of the motor that give influences to the motor performance.